DD-002 One stop dispensing: Nursing staff's initial experience with barcode controlled bedside medication dispensing. (14th February 2016) - Gede, DB; Gemmer, M; Andersen, SL; Assafi, L; Koch, JS; McNulty, HBØ; Andersen, MB
Abstract : Background: The patient role is changing to include further patient involvement, control and empowerment. To accommodate this new patient profile in new hospital construction projects, we tested the medication one stop dispensing (OSD) system. The OSD method involves medications stored in the patients' bedside lockers, and barcode controlled medication dispensing is performed by mobile dispensing units (MDU). This study presents the first national results for MDU. Purpose: To evaluate nursing staff's initial experiences with barcode controlled bedside medication dispensing. Material and methods: MDU was designed in November 2014 following an interdisciplinary workshop and produced by MedicSysteme. MDU was equipped with a laptop installed with the hospital's standard software for real time documentation and access to patient charts and the internet. A 2D bar code reader was connected for bar code verification in the medication dispensing and administration process. In January and February 2015, nursing staff from the orthopaedic surgery ward were trained for bedside dispensing using guided learning videos, peer to peer training and structured reviews of regional medication guidelines. A focus group interview was conducted in May 2015 with four nursing staff members with experience in drug dispensing. A semi-structured interview guide was applied and the interview was audio recorded, transcribed and thematically categorised through content analysis. Results: Qualitative thematic analysis of the interview identified the following topics: hardware, software, patient safety, patient involvement and workflow. The in-line process with bedside access to charts and drug information focuses on the patient's overall condition and treatment. The use of MDU and OSD invite patient involvement and reduce the risk of medication mix-up errors. Nursing staff experience more interruptions when dispensing at the bedside. Further development of suitable IT solutions and the physical appearance of the MDU are needed. This study found implementation barriers related to workflow and hospital décor, especially in 4-bed rooms. Conclusion: A focus group interview identified the following topics: hardware, software, patient safety, patient involvement and workflow. Future studies should focus on optimising MDU design and implementation of the new dispensing practice on a larger scale. No conflict of interest.